Current status of intestinal parasitosis and microsporidiosis in industrialized countries: Results from a prospective study in France and Luxembourg. - Maxime Moniot; Céline Nourrisson; Eloïse Bailly; Céline Lambert; Patricia Combes; Philippe Poirier (PLoS Neglected Tropical Diseases)
Background Human intestinal parasitosis and microsporidiosis are a global health concern, mostly in endemic areas but should not be neglected elsewhere. Recent nationwide epidemiological data are scarce, especially from primary health care and developed countries. Diagnosis by molecular tools are increasing and several commercial gastrointestinal panel assays including protozoans and/or helminths are now available. These news tools improve the knowledge into real human parasite epidemiology. This study provides an epidemiological update on intestinal parasites found in primary health care in France and Luxembourg. Methodology/principal findings Two thousand fifty-six stools from primary health care patients were analyzed for the presence of intestinal parasites (IPs) during two different seasons of 2022, the winter and the summer, corresponding to more than 1500 patients from all over France and Luxembourg. Parasite detection was performed combining standard microscopy (merthiolate-iodine-formaldehyde and Bailenger concentration procedures) with two molecular panel assays (AMPLIQUICK Fecal Pretreatment, AMPLIQUICK Protozoans and AMPLIQUICK Helminths, BIOSYNEX, France). The prevalence of IPs in primary care patients reached 33.2%. Blastocystis sp. and Dientamoeba fragilis were the most frequently detected parasites in 20.5% and 13.1% of patients, respectively. Coinfection with two or more parasites was detected in 9.9% of patients. For some parasites, patterns according to gender, age, geography or season have been observed. Conclusion/significance The high prevalence of pathogenic IPs (about 7%) underlines the importance of investigating gastrointestinal disorders through parasite examination, even in developed countries. The detection of parasites, pathogenic or not, remains a marker of the faecal-oral route of transmission and results should be interpreted accordingly. Parasites molecular characterization give new insights and should encourage further research as industrialized countries are not exempt of parasitic circulation and a better survey is necessary.